Students’ attitude and motivation in mathematical physics - Jufrida Jufrida; Wawan Kurniawan; Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan; Weni Angra Maya (International Journal of Evaluation and Research in Education (IJERE), 2019)
Attitude is one aspect that needs to be considered both for learning activities or learning objects. This study aims to determine the attitudes and motivations of students in mathematics physics subjects. The sample used was 100 students who had studied the Mathematics Physics course. This study employed quantitative research methods with correlational research design. Respondent was gathered by purposive sampling method. The research instruments used were attitude questionnaires in mathematical physics and motivational questionnaires. The study found that there is a significant relationship between attitudes and motivation of students in mathematics physics learning.